Suhu inkubasi, pasir pantai peneluran dan sukses penetasan telur penyu pada sarang semi alami di Pantai Warebar - Yenbekaki Distrik Waigeo Timur, Kabupaten Raja Ampat - Aditya P. Tarigan; Ricardo F. Tapilatu; Marthin Matulessy (Cassowary, 2020)
The research took place between May and October 2019, and divided into two stages. The first stage was field research to collect data by identifying turtles, calculating hatching successes, measuring the temperature of the nesting beach and nest temperature of each species of turtle in semi-natural nests at Warebar Beach, Yenbekaki village, East Waigeo Sub District, Raja Ampat. The second stage after the field was conducting an analysis of hatching rate in hatchery, sand temperature and nest temperature for each species of turtle. The species of turtles nesting at Warebar Beach are olive-ridley (Lepidochelys olivacea) and hawksbill (Eretmochelys imbricata) turtles. Based on the measurement results at semi-natural nests, it was obtained that the hatching rate of olive ridley sea turtle was 71.6%±28.3 (X±SD) and hawksbill sea turtle was 59.8%±41.3, the overall mean temperature of nesting beach was 28oC, the mean incubation temperature for both sea turtle species was 31oC.